ANALISIS PENGELOLAAN PIUTANG DAN POTENSI PIUTANG YANG TIDAK TERTAGIH SEBAGAI TINDAK LANJUT KEBIJAKAN PEMBAYARAN KREDIT PADA BIMBINGAN BELAJAR X DI MADIUN - Maya Novitasari; Rizka Hardiyanti (Universitas PGRI Madiun, 2017)
This study aims to analyze the management of receivables and the potential of uncollectible receivables as a follow-up policy of credit payments on the guidance of learning X in Madiun.Piutang is one type of accounting transactions that take care of consumer billing is owed to a person, a company, or an organization for goods And services that have been given to the consumer. This research uses experimental research method is research that deliberately researcher manipulation to one variable with a certain way so that influence on one or more other variable that measured. In addition, Gay (1981: 207-208) states that experimental research methods are the only research method that can correctly test hypotheses concerning causal relationships (causation). The results of research conducted at the Institute of Tutoring X in Madiun, the researcher concludes that the management of accounts receivable and uncollectible potentials in the institution of learning guidance X in Madiun there has been improvement in the new academic year 2016-2017. So that in the new academic year 2015-2016 is no longer any receivables that are not collectible, but there is still a policy of payment on credit that must be paid every maturity.Keywords : Receivables Management, Unsecured Accounts Receivable Potential and Follow-Up Credit Policy.